Third rail : an Eddy Harkness novel - Flynn, Rory, 1961- (Houghton Mifflin Harcourt, 2014)
Scapegoated for the death of a baseball fan, a brilliant young narcotics detective with a penchant for noticing elusive clues returns in disgrace to his Boston hometown only to be embroiled in a local investigator's drug-related search for a police-issue gun.